Electrophysiological method and interval model for identification the distance to reverse laryngeal nerve during surgery operation on the thyroid - Dyvak, Mykola; Pukas, Andriy (Видавництво Львівської політехніки, 2011)
The electrophysiological method and interval model for identification the distance to reverse laryngeal nerve during surgery operation on the thyroid was considered.
Keywords: laryngeal nerve; electrophysiological method; interval model; model identification